Detection of Group A Streptococcus from Pharyngeal Swab Samples by Bacterial Culture Is Challenged by a Novel mariPOC Point-of-Care Test - Vakkila, Jukka; Koskinen, Janne O.; Brandt, Annika; Muotiala, Anna; Liukko, Viivi; Soittu, Sari; Meriluoto, Siiri; Vesalainen, Marika; Huovinen, Pentti; Irjala, Kerttu (Journal of clinical microbiology, 2015)
mariPOC is a novel point-of-care test system for rapid detection of respiratory tract infections. We compared the performance of the mariPOC test to that of bacterial culture for detecting group A streptococcus (GAS) in 219 pharyngitis patients (ages 1–64 years) and 109 healthy asymptomatic controls (ages 19–69 years). In addition, 42 patient samples were analyzed by quantitative PCR (qPCR). Of the 219 pharyngeal patient samples, 32 were positive in a GAS bacterial culture (prevalence 15%) and 65 (30%) in the mariPOC test. The amount of GAS in samples reported positive by the mariPOC test and negative by culture was, on average, 10-fold less than that of those positive in both methods. This indicated that the negative results in bacterial cultures were due to lower sensitivity. The qPCR results were positive and in line with the mariPOC results in 43% of the discordant samples studied. Two GAS culture-positive samples were negative by the mariPOC test. The prevalences of GAS in the control subjects were 2% and 6% by culture and mariPOC results, respectively. We conclude that the mariPOC antigen detection test is more sensitive than the conventional bacterial culture for the detection of GAS among symptomatic pharyngitis patients. The higher prevalence of GAS by the mariPOC test among symptomatic patients was probably not due to carriership, since among the control patients, the difference in the prevalence of GAS by the mariPOC test and culture was not nearly as high, 15% versus 4%, respectively. Clinical trials are needed to show the clinical importance of our findings.